Treatment patterns after poly-ADP ribose polymerase (PARP) inhibitors in epithelial ovarian cancer patients. Issue 7 (23rd March 2022) - Sivakumaran, Tharani; Krasovitsky, Michael; Freimund, Alison; Lee, Yeh Chen; Webber, Kate; So, Jane; Norris, Christie; Friedlander, Michael; Mileshkin, Linda; Au-Yeung, George
Abstract : Objectives: The primary objective of this study was to describe treatment patterns after poly-ADP ribose polymerase (PARP) inhibitor in patients with epithelial ovarian cancer. Secondary objectives were to evaluate duration of response, time to first subsequent therapy, progression-free survival and overall survival. Methods: This was a retrospective analysis of patients with epithelial ovarian cancer treated with PARP inhibitor therapy at six Australian gynecological oncology centers. Eligible patients were identified via clinics, trial databases and pharmacy dispensing logs between January 2005 and September 2019. Information regarding clinico-pathological characteristics and treatment outcomes were collated from medical records. Results: A total of 85 patients with epithelial ovarian cancer were identified. Of these, 61% had germline BRCA1/2 mutations, 9% had somatic BRCA1/2 mutations, 5% had confirmed homologous recombination deficiency and 25% were BRCA1/2 wildtype mutations. A total of seventy-seven (91%) patients received chemotherapy after PARP inhibitor, with fifty-six (72.7%) of these patients receiving platinum-based chemotherapy. Four patients (5%) had a complete response, 15 (20%) a partial response, 15 (20%) stable disease and 41 (55%) progressive disease. Median duration of response to chemotherapy was 7.0 months (range 0.2–20.4). Median time to first subsequent therapy was 17.6 and 15.1 months in patients who received a PARP inhibitor as maintenance therapy and treatment, respectively. Median progression-free survival of first line treatment after PARP inhibitor was 9.6, 3.5 and 4.6 months for platinum doublet, single agent platinum and non-platinum chemotherapy, respectively. Adjusting for age and FIGO (Federation of Gynecological Oncologists classification) stage progression-free survival did not differ between treatment groups (p=0.14). Median overall survival for the cohort was 69 months, and patients with platinum sensitive ovarian cancer had improved survival compared with those with platinum refractory or resistant disease. Conclusion: Platinum doublet chemotherapy resulted in non-significant improved progression-free survival compared with other regimens, suggesting potential independent mechanisms of resistance between PARP inhibitor and platinum compounds.